Consent in Marriage and the Impact of Prevention (ʿAdhl) and Compulsion: A Comparative Jurisprudential Study - Seraj aldden mohammed elbahi Ali alobaid (Journal of Libyan Academy Bani Walid, 2025)
This research aims to highlight the importance of consent in marriage contracts as a fundamental pillar of legally and religiously valid marriages. It examines and analyses the issues of coercion and compulsion as two of the most prominent obstacles affecting a person’s choice in marriage and the achievement of satisfaction. The research begins by establishing the concept of consent in language and terminology, explaining that it is a psychological state that indicates peace of mind and acceptance of an action without coercion, and that it is the foundation upon which the marital relationship in Islam is built. It then addressed the issue of coercion as the guardian’s unjustified prevention of a woman from marrying the person she desires and who is suitable for her, pointing out that the Holy Qur’an and the Sunnah of the Prophet explicitly prohibit this act, and that the jurists have unanimously agreed that the judge has the right to marry a woman if her guardian unjustly refuses to do so. Libyan law has recognized this ruling in Article 8 of Law No. 10 of 1984, which prohibits azl and allows the judge to marry a woman in cases where it is proven. The research also discussed coercion in marriage, highlighting the difference between jurists who permit it in the case of a father over his unmarried daughter, those who prohibit it absolutely, and the choice of Libyan law to adopt the opinion that prohibits coercion absolutely and makes marriage based on mutual consent between the parties and the guardian. The research concluded that consent is a fundamental condition for the validity of a marriage contract. It also emphasized the harmony of Libyan legislation with these principles of Islamic law by prohibiting coercion and compulsion and recognizing women’s freedom to marry whomever they choose, to preserve their dignity and the stability of the family and society.